Spore coat protein and enterotoxin synthesis in Clostridium perfringens. - Labbe, R G (1977)
Polyacrylamide gel profiles of Clostridium perfringens spore coat protein revealed four and occasionally five components. Pulse-chase experiments indicated that synthesis of coat protein polypeptide and enterotoxin was an early sporulation event. However, maximum synthesis occurred coincident with the onset of heat resistance.